2017
DOI: 10.1371/journal.pone.0173098
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that agricultural use of pesticides selects pyrethroid resistance within Anopheles gambiae s.l. populations from cotton growing areas in Burkina Faso, West Africa

Abstract: Many studies have shown the role of agriculture in the selection and spread of resistance of Anopheles gambiae s.l. to insecticides. However, no study has directly demonstrated the presence of insecticides in breeding sources as a source of selection for this resistance. It is in this context that we investigated the presence of pesticide residues in breeding habitats and their formal involvement in vector resistance to insecticides in areas of West Africa with intensive farming. This study was carried out fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 28 publications
2
71
0
Order By: Relevance
“…Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both 12, 13, 14, 15, 16 although in other locations evidence of higher resistance after the introduction these interventions was not found 12, 17 . Associations between agricultural pesticide use and insecticide resistance have also been found 11, 18 , and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae 19 . Relationships between resistance and drivers of selection will, however, vary geographically depending on population structure 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both 12, 13, 14, 15, 16 although in other locations evidence of higher resistance after the introduction these interventions was not found 12, 17 . Associations between agricultural pesticide use and insecticide resistance have also been found 11, 18 , and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae 19 . Relationships between resistance and drivers of selection will, however, vary geographically depending on population structure 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to practices linked to intensification of agriculture, resistance to insecticides has emerged and spread [10]. Several studies suggest that intensive use of insecticides in agriculture selects for resistant genes in malaria vectors [11,12]. Although research has been conducted previously on farmers' knowledge, attitudes, practices and beliefs (KAPB) on insecticides used in agriculture [10,12], there is a paucity of studies on people's knowledge about resistance to currently utilized insecticides and the causes leading to resistance, including how people cope with the growing resistance.…”
Section: Introductionmentioning
confidence: 99%
“…gambiae s.s , the kdr-w frequencies have always been high in this species in Southwest Burkina Faso [7,9,55] indicating that the mutation has a low cost for this species or that strong selection pressures occur, such vector control strategies implementation (universal distribution of LLINs is implemented in Burkina Faso since 2010 [56]) and massive use of pesticides in agriculture [57]. Indeed, the intensive use of insecticides in cotton cultivation would be a major factor driving the selection of pyrethroid-resistant specimens in Southwest Burkina Faso [9]. Most of the populations of An.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that LLINs have contributed to 68 % of the decline in malaria cases observed between 2000 and 2015 [5] despite moderate use rates [6]. However, the emergence of physiological [79] and behavioral [10,11] insecticide resistance mechanisms in Anopheles mosquitoes, as observed in most parts of Africa, could compromise the effectiveness of LLINs and explains the recent rebound in malaria cases.…”
Section: Introductionmentioning
confidence: 99%